2003
DOI: 10.1086/375330
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Fluctuation Power Spectral Densities of Seyfert 1 Galaxies

Abstract: By combining complementary monitoring observations spanning long, medium and short time scales, we have constructed power spectral densities (PSDs) of six Seyfert 1 galaxies. These PSDs span 4 orders of magnitude in temporal frequency, sampling variations on time scales ranging from tens of minutes to over a year. In at least four cases, the PSD shows a "break," a significant departure from a power law, typically on time scales of order a few days. This is similar to the behavior of Galactic X-ray binaries (XR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
436
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 276 publications
(474 citation statements)
references
References 56 publications
37
436
1
Order By: Relevance
“…These XMM-Newton data are somewhat insensitive to the low-frequency slope -however, we find it to be constrained to α1 = 0.9 +0.3 −0.1 , which is consistent with the value of 1 typically found from long-term monitoring campaigns (e.g. Uttley, McHardy & Papadakis 2002, Markowitz et al 2003, McHardy et al 2006. The high-frequency slope has a best-fitting value of α2 = 3.5 +0.4 −0.3 , consistent with the average value of 3.08 obtained from a sample of 15 Seyfert galaxies by González-Martín & Vaughan (2012).…”
Section: The Power Spectrumsupporting
confidence: 86%
See 1 more Smart Citation
“…These XMM-Newton data are somewhat insensitive to the low-frequency slope -however, we find it to be constrained to α1 = 0.9 +0.3 −0.1 , which is consistent with the value of 1 typically found from long-term monitoring campaigns (e.g. Uttley, McHardy & Papadakis 2002, Markowitz et al 2003, McHardy et al 2006. The high-frequency slope has a best-fitting value of α2 = 3.5 +0.4 −0.3 , consistent with the average value of 3.08 obtained from a sample of 15 Seyfert galaxies by González-Martín & Vaughan (2012).…”
Section: The Power Spectrumsupporting
confidence: 86%
“…'Xray time lags') 1 which are routinely observed to display similar behaviour but with their frequencies and amplitudes roughly scaled inversely with black hole mass (e.g. Lawrence et al 1987;Uttley, McHardy & Papadakis 2002;Markowitz et al 2003;McHardy et al 2004;McHardy et al 2006;Arévalo et al 2008). Additionally, the rms amplitude of X-ray variability is commonly observed to scale linearly with the flux of the source (i.e.…”
Section: Introductionmentioning
confidence: 92%
“…One of our main targets is NGC 4051 and results from the first 1.5 years of observation (M c Hardy et al 1998) indicated that the slope at low frequencies was probably flatter than that at high frequencies but neither the break frequency, or the slopes, were particularly well defined. Edelson and Nandra (1999), Pounds et al (2001) and Markowitz et al (2003) have all now demonstrated PSD flattening in other AGN at low frequencies, using RXTE data.…”
Section: Introductionmentioning
confidence: 87%
“…However in most other AGN only one break has been found and, although the slopes below the break are not that well defined (eg Uttley et al 2002;Markowitz et al 2003), in general they are closer to -1 than to zero. However it is not clear whether these breaks correspond to the high frequency break in low state systems or the single break in high state systems.…”
Section: Introductionmentioning
confidence: 99%
“…White noise uniformly affects power spectra across all frequencies or periods, and it is accounted for by a uniform confidence level. A growing body of examples across a range of astrophysical phenomena, including X-ray binaries (van der Klis, 1995), Seyfert galaxies (Lawrence et al, 1987;Markowitz et al, 2003), gamma-ray bursts (Ukwatta et al, 2009;Cenko et al, 2010), and quasiperiodic pulsations (QPPs) during solar flares (e.g. Inglis, Ireland, and Dominique, 2015) yield power-law-like spectra.…”
Section: Introductionmentioning
confidence: 99%